Implementasi Dashboard Multiplatform Monitoring Sales Berbasis Web Menggunakan Metode Functional Requirements (Studi Kasus : PT. Axindo Infotama) - Adam Pamungkas; Irpan Kusyadi (CV. Multi Kreasi Media, 2022)
The design of a web-based sales monitoring dashboard is an application that is used to make it easier to monitor sales and outlet performance. Previously, management had monitored the performance of sales and outlets. However, in the process of monitoring sales and outlets, there are still some obstacles that make management take time and the process carried out is still relatively manual, such as the sales process by writing on notes and invoices for the sale of goods is still done manually, namely by writing on notes and invoices to be given to management. With the large number of outlets managed by sales, it makes it difficult for admins to recapitulate sales and outlet achievements, so it takes a lot of time to recapitulate. In addition, in monitoring the performance of sales and data outlets, it has not been in the form of data visualization. So it is expected to facilitate management in monitoring sales and outlets. Data collection was carried out through interviews, observations and literature studies. The application development process uses the Functional requirements method. Fucntional Requirements include user alerts about newly added ones, can categorize content and have an efficient search process. Website-based applications are built using the JavaScript Programming language and node frameworks.js as a helper to solve problems, making the process of monitoring sales and outlets easier that can streamline management performance. Based on the results of the design, implementation and testing of the multiplatform sales monitoring dashboard implementation system, the following conclusions can be drawn: the multiplatform sales monitoring dashboard implementation system can facilitate management in recapitulating sales and outlet data. This application is expected to be used and applied to PT. Axindo Infotama.